Konsep Zuhud dalam Kepemilikan Harta Perspektif Ekonomi Syariah - Moh. Irham Maulana; Sagita Martha Triyani; Armeita Anik Sukowati (Program Studi Perbankan Syariah Sekolah Tinggi Agama Islam Salahuddin Pasuruan, 2022)
Wealth is something that humans want to have for various purposes and needs, be it basic needs, shopping, bus iness and social needs. The sense of belonging to the wealth that affects whether the property will have a positive or negative impact on the surrounding area. The concept of zuhud which is often known in Sufistic knowledge can also be very good if used in wealth ownership. Because someone who uses the concept of zuhud in wealth ownership will be more oriented to the world, not to the world. So that the purpose of finding and owning property is only as a means to achieve its ultimate goal in the world, namely to add goodness to Allah, carry out Islamic Shari'ah and worship Allah.